Anti-cult legislation in the United States of America - Matković Aleksandar (Pravni Zapisi, 2016)
The United States of America are one of the rare states (and according to available data, the first one), which introduced specialised anti-cult regulations. This article is dedicated to the analysis of the general perspective of the origins and reasons for the introduction of such regulations in the USA, to their presentation and the analysis of their content, as well as identification of their key specific and general characteristics. First, the author analyses the influences and reasons which led to the introduction of mentioned legislation. The author points to the direct link between the phenomenon of Satanist moral panic and the anti-cult movement, on one side, and anti-cult legislation, on the other. Through an observation of legislation passed in federal states of Idaho, California and Illinois, he identifies their specific features, as well as general, common characteristics. It was ascertained that Idaho's legislation, which was passed first, served as a model for other adopted legal acts. Further on, it was concluded that the main negative characteristics of USAs anti-cult legislation are: the absence or lack of foundation for their adoption; the controversies in their practical application; the absence of expected social results; their arguable compatibility with legally guaranteed religious rights and freedoms; the creation of a perspective for legalisation of discrimination on religious grounds; and the possibility and justifiability of application of general legislation which does not have a specialised, i.e. anti-cult orientation.